Dietary intake and urinary excretion of Maillard reaction products (MRPs) - A. Förster; Y. Kühne; T. Henle (Czech Journal of Food Sciences, 2004)
The aim of our study was to investigate the influence of nutrition on the urinary excretion of Amadori products, pyrraline and pentosidine in a dietary study involving 18 healthy volunteers. Starting with day two, participants had to avoid Maillard product containing food for a period of 7 days, followed by day nine without dietary restrictions. Samples of 24 h-urine were collected and analysed for free furosine, pyrraline and pentosidine using dedicated chromatographic methods. For all MRPs, a significant decrease in the amount excreted with urine was observed due to the MRP-free diet. Urinary excretion of free pyrraline and fructoselysine, which was calculated from furosine analysis, were lowered about 90% from 3.9 ± 1.4 mg/d to 0.4 ± 0.3 mg/d and 7.2 ± 4.1 mg/d to 0.9 ± 0.2 mg/d, respectively. Urinary excretion of free pentosidine was only in the μg/d range and its decrease added up to 50% from 7.3 ± 3.7 μg/d to 3.4 ± 1.1 μg/d. These results indicate that renal excretion of MRPs is directly affected by dietary intake of those. With respect to the daily intake via heated foods, mainly as proteinbound derivatives, pyrraline seems to be of better bioavailability than the Amadori product and pentosidine. This points to different metabolic pathways. Whereas metabolic transformation of AGEs may quantitatively be of little importance, the major part of ingested Amadori products seems to be degraded in vivo.